DESKRIPSI KEMANDIRIAN PESERTA DIDIK SELAMA SCHOOL FROM HOME (SFH) PADA MASA PANDEMI COVID19 - Gemilang, Fhajri Arye; Rezkiki, Fitrianola; Kartika, Imelda R; Fakhri, Fakhri; Meiyersi, Heru (Psikoislamedia: Jurnal Psikologi, 2021)
The temporary closure of educational institutions in an effort to contain the spread of COVID-19 has affected millions of Indonesian students. Starting from March 16, 2020, face-to-face learning activities in schools were officially suspended by the Government and replaced with School from Home. SMP/MTs/equivalent were affected with 13,086,424 students studying at home. The government facilitates learning programs from home (virtual face-to-face), but this sudden activity causes students, parents and teachers to not fully implement it so that it has an impact on the independence of students. This study aims to determine the description of the independence of students during School from Home. The design of this research is quantitative with analytical descriptive approach, the sample is 284 people (accidental sampling). The instrument used is an independence questionnaire adapted from Siregar (2018). It was found that most of the respondents (54.5%) had low independence. This is greatly influenced by the condition of parents, teachers, and supporting facilities for learning at home which need a lot of adjustments, so it is hoped that the school will be able to increase the learning independence of students.